2016
DOI: 10.5935/0946-5448.20160019
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia treatment by platelet rich plasma injection

Abstract: Based on our results, platelet rich plasma administration to the olfactory region could be a promising, last chance therapy for complete anosmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 11 publications
4
28
0
1
Order By: Relevance
“…In our pilot study, only a single PRP injection was performed to first assess the safety and feasibility of this therapy. Mavrogeni and colleagues described four PRP injections with 4‐week intervals in between without any safety concerns . Taking this together with our findings from this study, future studies may benefit from multiple PRP treatments.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In our pilot study, only a single PRP injection was performed to first assess the safety and feasibility of this therapy. Mavrogeni and colleagues described four PRP injections with 4‐week intervals in between without any safety concerns . Taking this together with our findings from this study, future studies may benefit from multiple PRP treatments.…”
Section: Discussionsupporting
confidence: 65%
“…The role of PRP on olfactory neuroregeneration and related inflammation is unknown, but a preliminary animal study showed potential functional benefits of topical PRP in an anosmia induced mouse model . One pilot study evaluated PRP for hyposmia in humans and reported subjective improvements in five patients following treatment . However, that study lacked quantitative measurements of olfaction pre‐ and post‐treatment and other standardized norms.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its advantages in wound healing, angiogenesis, use as glue material, post-operative pain and bleeding, PRP is also one of the interesting materials in otorhinolaryngology and head and neck surgery. A significant improvement in odor function was observed following platelet-rich plasma injection treatment applied in patients with anosmia [18].…”
mentioning
confidence: 94%
“…PRP was first used in 2016 by Mavrogeni et al [18], based on the view that platelets can accelerate the regeneration of the olfactory nerves in anosmia patients by secreting various growth factors and active metabolites, especially transforming growth factor. Following the application of PRP in the olfactory area of 5 patients with idiopathic anosmia in 4 sessions, the sense of smell returned in 4 patients and one patient stated that he could smell a little but could not smell all.…”
mentioning
confidence: 99%
See 1 more Smart Citation